Infection prevention requirements for the medical care of immunosuppressed patients: recommendations of the Commission for Hospital Hygiene and Infection Prevention (KRINKO) at the Robert Koch Institute - Commission for Hospital Hygiene and Infection Prevention (KRINKO) (German Medical Science GMS Publishing House, 2022)
In Germany, guidelines for hygiene in hospitals are given in form of recommendations by the Commission for Hospital Hygiene and Infection Prevention (Kommission für Krankenhaushygiene und Infektionsprävention, "KRINKO"). The KRINKO and its voluntary work are legitimized by the mandate according to § 23 of the Infection Protection Act (Infektionsschutzgesetz, "IfSG").The original German version of this document was published in February 2021 and has now been made available to the international professional public in English. The guideline provides recommendations on infection prevention and control for immunocompromised individuals in health care facilities. This recommendation addresses not only measures related to direct medical care of immunocompromised patients, but also management aspects such as surveillance, screening, antibiotic stewardship, and technical/structural aspects such as patient rooms, air quality, and special measures during renovations.